Tantalum carbide slurry and preparation method thereof, tantalum carbide coating and tantalum carbide product
By mixing tantalum carbide powder with spherical tantalum carbide particles and sintering aids, wet ball milling is used to prepare tantalum carbide slurry, which solves the problems of many pores and prone to cracking in the traditional tantalum carbide coating, and achieves high relative density and sintering activity. Tantalum carbide coating.
Patent Information
- Application Number
- CN202411288985.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-03
AI Technical Summary
In the traditional tantalum carbide coating preparation method, there are problems such as many pores, easy cracking and low relative density of the coating, resulting in low reliability.
The tantalum carbide slurry is prepared by mixing the tantalum carbide powder with spherical tantalum carbide particles, sintering aids and nonionic polymer binder, and a wet ball mill is used to prepare the tantalum carbide slurry. Combined with spray drying and low-temperature presintering treatment, it forms a high sintering activity Tantalum carbide coating.
Effectively reduce coating pores, improve relative density, enhance the sintering activity and viscosity of tantalum carbide coating, ensure the brushing performance of high solid phase content slurry, and form a high-performance tantalum carbide coating.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of high-performance coatings, and in particular to a tantalum carbide slurry and a preparation method thereof, a tantalum carbide coating and a tantalum carbide product. Background Art
[0002] Tantalum carbide (TaC) has excellent high-temperature mechanical stability, high-temperature corrosion resistance, and ablation resistance. It is a key material for the preparation of carbon-based crucible coatings and high-temperature ceramics for semiconductors.
[0003] At present, the methods commonly used to prepare high-performance tantalum carbide coatings mainly include sintered tantalum carbide coatings and chemical vapor deposition. The tantalum carbide coating prepared by chemical vapor deposition has the advantages of uniform thickness, controllable grain structure, and high purity, but the equipment required for this method is expensive and the operating cost is high. The prepared coating is also prone to cracks and pores, resulting in low reliability of the tantalum carbide coating.
[0004] Sintered tantalum carbide coating has the advantages of simple operation, low cost, and mass production, and is the preferred method for preparing high-performance tantalum carbide coating. Sintered tantalum carbide coating mainly uses organic slurry with high solid content, that is, tantalum carbide powder particles and a small amount of sintering aid are dispersed in an organic solvent; then the organic slurry is sprayed or brushed on the surface of the substrate, and the tantalum carbide coating can be obtained after high-temperature sintering. However, sintered tantalum carbide coating also has the problems of more pores in the coating, easy cracking of the coating, and low relative density of the coating.
[0005] Therefore, the traditional technology still needs to be further improved. Summary of the invention
[0006] Based on this, one or more embodiments of the present application provide a tantalum carbide slurry and a preparation method thereof, a tantalum carbide coating, and a tantalum carbide product that can reduce coating porosity or cracking and increase the relative density of the coating.
[0007] According to a first aspect of an embodiment of the present application, a method for preparing a tantalum carbide slurry is provided, comprising the following steps:
[0008] Mixing tantalum carbide powder and a binder to obtain a first slurry;
[0009] The first slurry is subjected to spray drying, first screening, pre-sintering and second screening in sequence to obtain spherical tantalum carbide particles; the particle size of the spherical tantalum carbide particles is 10 μm to 30 μm;
[0010] The spherical tantalum carbide particles are mixed with the tantalum carbide powder, a sintering aid, a non-ionic polymer binder and an organic solvent to obtain a mixture; the particle size of the tantalum carbide powder is 0.05 μm to 0.5 μm;
[0011] The mixture is wet-milled to obtain tantalum carbide slurry.
[0012] In one embodiment, the mixture includes, by weight percentage: 65 to 80 parts of spherical tantalum carbide particles, 5 to 20 parts of tantalum carbide powder, 0.5 wt % to 1 part of sintering aid, 0.5 to 1 part of non-ionic polymer binder and 8 to 14 parts of organic solvent.
[0013] In one embodiment, the mixture includes, by weight percentage: 70 to 75 parts of spherical tantalum carbide particles, 15 to 18 parts of tantalum carbide powder, 0.7 wt % to 1 part of sintering aid, 0.6 to 0.8 parts of non-ionic polymer binder and 8.2 to 10.7 parts of organic solvent.
[0014] In one embodiment, the particle size of the tantalum carbide powder is 0.1 μm to 0.5 μm.
[0015] In one embodiment, the tantalum carbide slurry satisfies at least one of the following conditions:
[0016] (1) The sintering aid is selected from one or more of tantalum disilicide, molybdenum disilicide, pyrolytic carbon black, aluminum oxide and yttrium oxide;
[0017] (2) The particle size of the sintering aid is 0.5 μm to 5 μm;
[0018] (3) The organic solvent is selected from one or more of ether, anhydrous ethanol, butanone, n-octanol, triolein, toluene, xylene and isopropanol;
[0019] (4) The nonionic polymer binder is selected from one or more of polyacrylamide, polyethylene oxide, polyurethane, polyvinyl alcohol, polyaniline and polyethylene terephthalate.
[0020] In one embodiment, the preparation method satisfies at least one of the following conditions:
[0021] (1) In the wet ball milling step, the ball milling time is 2 h to 6 h, the ball to material ratio is (1 to 5):1, and the rotation speed is 50 r / min to 500 r / min;
[0022] (2) The temperature of the spray drying process is 80°C to 120°C;
[0023] (3) The pre-sintering temperature is 1200°C to 1600°C, and the holding time is 30min to 120min;
[0024] (4) The mesh sizes of the first screening and the second screening are independently selected from 500 mesh to 1250 mesh.
[0025] In one embodiment, the preparation method satisfies at least one of the following conditions:
[0026] (1) The binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, methyl cellulose and polyacrylic acid;
[0027] (2) Based on the mass of the tantalum carbide powder in the first slurry, the amount of the binder added is 0.1wt%~0.5wt%.
[0028] According to a second aspect of an embodiment of the present application, a tantalum carbide slurry is provided, which is prepared by the above-mentioned method for preparing tantalum carbide slurry.
[0029] According to a third aspect of an embodiment of the present application, a tantalum carbide coating is provided, wherein a raw material for preparing the tantalum carbide coating includes the above-mentioned tantalum carbide slurry.
[0030] According to a fourth aspect of an embodiment of the present application, a tantalum carbide product is provided, comprising the above-mentioned tantalum carbide coating.
[0031] Compared with the traditional technology, this application has the following beneficial effects:
[0032] The present application prepares spherical tantalum carbide particles with excellent sintering activity by granulating and pre-sintering tantalum carbide powder at low temperature; the spherical tantalum carbide particles are matched with tantalum carbide powder, so that the tantalum carbide slurry has good sintering activity. At the same time, the spherical tantalum carbide particles with relatively large particle size are matched with a small amount of tantalum carbide powder with relatively small particle size in a specific ratio, which can effectively increase the powder solid content of the tantalum carbide slurry without affecting the viscosity of the tantalum carbide slurry, thereby ensuring the brushing performance of the slurry with high solid content. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0035] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0036] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0037] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0038] A first aspect of the present application provides a method for preparing tantalum carbide slurry, comprising steps S10 to S40.
[0039] Step S10: Mix tantalum carbide powder and a binder to obtain a first slurry.
[0040] Step S20: spray drying, first screening, pre-sintering and second screening are sequentially performed on the first slurry to obtain spherical tantalum carbide particles; the particle size of the spherical tantalum carbide particles is 10 μm to 30 μm.
[0041] Step S30: mixing spherical tantalum carbide particles with tantalum carbide powder, a sintering aid, a non-ionic polymer binder and an organic solvent to obtain a mixture; the particle size of the tantalum carbide powder is 0.05 μm to 0.5 μm.
[0042] Step S40: wet ball milling the mixture to obtain tantalum carbide slurry.
[0043] Unless otherwise specified, the particle size in this application refers to D 50 Particle size.
[0044] The mass fraction of tantalum carbide in traditional tantalum carbide slurry is generally below 80wt%, and the volume fraction of ceramic powder in the slurry prepared in this way is usually only 30vol%~40vol%, while the volume fraction of organic solvent is as high as 60vol% and above, which easily leads to the volatilization of organic solvent in tantalum carbide coating after spraying or painting, resulting in coating shrinkage, cracking of coating and reducing the integrity of coating. At the same time, increasing the particle size of powder particles in slurry can increase the solid content of slurry to a certain extent, but coarse particles will reduce the sintering driving force of powder, thereby reducing the relative density of sintered coating.
[0045] The sintering activity of tantalum carbide powder and the solid content of slurry are a pair of contradictions, that is, the finer the powder, the higher the sintering activity, but the more difficult it is to obtain an organic slurry with a high solid content. The particle size of the powder in the traditional tantalum carbide slurry is generally 100nm~300nm to ensure its sintering activity; while the ultrafine powder has a high specific surface area, is very easy to agglomerate, and is difficult to disperse evenly. If the particle size of the powder is increased to 2~5 microns, the agglomeration phenomenon can be effectively improved, and the solid content of the tantalum carbide powder in the organic slurry can be increased, but this will significantly reduce the sintering activity of the tantalum carbide powder, thereby reducing the relative density of the tantalum carbide coating.
[0046] The present application sprays the first slurry into a granulation tower for atomization to obtain nearly spherical particles with a particle size of 10 μm to 30 μm, and performs a low-temperature pre-sintering treatment on the particles to ensure that they still have a high sintering activity similar to that of tantalum carbide powder. Low-temperature sintering only slightly promotes the sintering contact of the powder surface of tantalum carbide powder, so that its sintering activity is still higher than that of micron-sized tantalum carbide powder.
[0047] Furthermore, the present application combines spherical tantalum carbide particles with larger particle sizes and tantalum carbide powder with smaller particle sizes in a specific ratio, which can effectively increase the powder solid content of the tantalum carbide slurry without affecting the viscosity of the tantalum carbide slurry, thereby ensuring the brushing performance of the high solid content slurry.
[0048] In some embodiments, in step S10, the binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, methyl cellulose and polyacrylic acid.
[0049] In some embodiments, based on the mass of the tantalum carbide powder in the first slurry, the amount of the binder added is 0.1 wt % to 0.5 wt %.
[0050] As an example, the added amount of the binder may be 0.1 wt%, 0.11 wt%, 0.12 wt%, 0.13 wt%, 0.14 wt%, 0.15 wt%, 0.16 wt%, 0.17 wt%, 0.18 wt%, 0.19 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt% or 0.5 wt%.
[0051] In some embodiments, in step S20, the temperature of the spray drying process is 80°C to 120°C.
[0052] As an example, the temperature of the spray drying process can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.
[0053] In some embodiments, in step S20, the temperature of the pre-sintering treatment is 1200° C. to 1600° C., and the holding time is 30 min to 120 min.
[0054] As an example, the temperature of the pre-sintering process may be 1200° C., 1210° C., 1220° C., 1230° C., 1240° C., 1250° C., 1260° C., 1270° C., 1280° C., 1290° C., 1300° C., 1350° C., 1400° C., 1450° C., 1500° C., 1550° C., or 1600° C. The holding time may be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, or 120 min.
[0055] In some embodiments, in step S20, the mesh sizes of the first screening and the second screening are independently selected from 500 mesh to 1250 mesh.
[0056] In step S30 of the present application, the particle size of the spherical tantalum carbide particles is 10 μm to 30 μm, that is, the minimum and maximum values in the range of 10 μm to 30 μm, and each value between the minimum and maximum values, for example: 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm or 30 μm.
[0057] In step S10 and step S30 of the present application, the particle size of the tantalum carbide powder is 0.05 μm to 0.5 μm, that is, the minimum value and the maximum value in the range of 0.05 μm to 0.5 μm, and each value between the minimum value and the maximum value, for example: 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm or 0.5 μm.
[0058] In some optional embodiments, the particle size of the tantalum carbide powder is 0.1 μm-0.5 μm.
[0059] In some embodiments, in step S30, the mixture includes, by mass percentage, 65 to 80 parts of spherical tantalum carbide particles, 5 to 20 parts of tantalum carbide powder, 0.5 wt % to 1 part of sintering aid, 0.5 to 1 part of non-ionic polymer binder, and 8 to 14 parts of organic solvent.
[0060] In some optional embodiments, in step S30, the mixture includes, by mass percentage: 70 to 75 parts of spherical tantalum carbide particles, 15 to 18 parts of tantalum carbide powder, 0.7 wt % to 1 part of sintering aid, 0.6 to 0.8 parts of non-ionic polymer binder and 8.2 to 10.7 parts of organic solvent.
[0061] It can be understood that controlling the mass percentage of each component within the above-mentioned specific range can further improve the relative density of the prepared tantalum carbide coating.
[0062] In some embodiments, in step S30, the sintering aid is selected from one or more of tantalum disilicide, molybdenum disilicide, pyrolytic carbon black, aluminum oxide and yttrium oxide.
[0063] In some embodiments, in step S30, the particle size of the sintering aid is 0.5 μm to 5 μm; as an example, the particle size of the sintering aid can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.
[0064] In some embodiments, in step S30, the organic solvent is selected from one or more of diethyl ether, anhydrous ethanol, butanone, n-octanol, triolein, toluene, xylene and isopropanol.
[0065] In some embodiments, in step S30, the non-ionic polymer binder is selected from one or more of polyacrylamide, polyethylene oxide, polyurethane, polyvinyl alcohol, polyaniline and polyethylene terephthalate.
[0066] In some embodiments, in step S40, the ball milling time in the wet ball milling step is 2 h to 6 h, the ball to material ratio is (1 to 5): 1, and the rotation speed is 50 r / min to 500 r / min.
[0067] As an example, the ball milling time can be but not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h; the ball-to-material ratio can be but not limited to 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1; the rotation speed can be but not limited to 50r / min, 60r / min, 70r / min, 80r / min, 90r / min, 100r / min, 150r / min, 200r / min, 250r / min, 300r / min, 350r / min, 400r / min, 450r / min or 500r / min.
[0068] The tantalum carbide slurry prepared by the method of the present application has the advantages of high solid content and good sintering activity; after sintering, it can form a tantalum carbide coating with a relatively high density, which is suitable for materials such as carbon-based crucibles, graphite crucibles and high-temperature ceramics.
[0069] The second aspect of the present application provides a tantalum carbide slurry prepared by the preparation method of the first aspect.
[0070] The tantalum carbide slurry can reduce the porosity or cracking of the tantalum carbide coating and increase the relative density of the coating.
[0071] In a third aspect of the present application, a tantalum carbide coating is provided, and the raw materials for preparing the tantalum carbide coating include the tantalum carbide slurry of the second aspect mentioned above.
[0072] It can be understood that the above-mentioned tantalum carbide slurry is sintered at high temperature to obtain a tantalum carbide coating.
[0073] In a fourth aspect of the present application, a tantalum carbide product is provided, comprising a substrate and the tantalum carbide coating according to the third aspect.
[0074] In some embodiments, the thickness of the tantalum carbide coating in the tantalum carbide product is 50 μm to 200 μm.
[0075] It can be understood that the tantalum carbide coating is disposed on the surface of the substrate; further, the tantalum carbide coating is disposed on the inner surface and the outer surface of the substrate body.
[0076] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0077] Example 1
[0078] (1) Tantalum carbide powder with a particle size of 0.1 μm and a purity of 99.99% is mixed with polyvinyl alcohol to obtain a first slurry; the first slurry is then sprayed into a granulation tower by a sprayer for spray drying to obtain spherical tantalum carbide particles with good fluidity; granulated powder is obtained after drying; a sieve with a mesh size of 500 to 800 is then used for the first screening to obtain spherical tantalum carbide powder with a particle size of 20 μm to 30 μm. The amount of polyvinyl alcohol added is 0.1 wt% of the mass of the tantalum carbide powder; the spray drying temperature is 100°C.
[0079] (2) The spherical tantalum carbide powder obtained in step (1) is placed in a calcining furnace for pre-sintering at a temperature of 1200° C. and a holding time of 120 min. After pre-sintering, a sieve with a mesh size of 500 to 800 is used for a second screening to obtain spherical tantalum carbide particles with a particle size of 20 μm to 30 μm.
[0080] (3) Weigh the following raw materials by mass: 65 parts of the spherical tantalum carbide particles prepared in step (2), 20 parts of D 50 Tantalum carbide powder with a particle size of 0.1 μm, 0.5 parts of tantalum disilicide (TaSi 2 ) powder, 0.5 parts of polyvinyl alcohol, 14 parts of triolein, the total amount is 100 parts.
[0081] The above raw materials were mixed and wet ball milled, wherein the ball milling time was 3 hours, the ball-to-material ratio was 1:1, and the rotation speed was 100 r / min; tantalum carbide slurry was prepared. The solid content of the above tantalum carbide slurry was calculated to be 85wt%; specifically, the solid content in this application was obtained by calculating the percentage of the total mass of the particles and powder to the total mass of the slurry.
[0082] (4) The organic slurry prepared in the above step (3) was used to prepare a sintered tantalum carbide coating on the surface of a graphite crucible. The sintering temperature was 2100° C. and the holding time was 60 min. The thickness of the prepared tantalum carbide coating was 100 μm and the relative density was 98.7%. The coating quality was intact and there were no defects such as cracks.
[0083] Example 2
[0084] (1) Tantalum carbide powder with a particle size of 0.2 μm and a purity of 99.99% is mixed with polyacrylamide to obtain a first slurry; the first slurry is then sprayed into a granulation tower by a sprayer for spray drying to obtain spherical tantalum carbide particles with good fluidity; granulated powder is obtained after drying; a sieve with a mesh size of 800 to 1000 is then used for the first screening to obtain spherical tantalum carbide powder with a particle size of 15 μm to 20 μm. The amount of polyvinyl alcohol added is 0.5 wt% of the mass of the tantalum carbide powder; the spray drying temperature is 100°C.
[0085] (2) The spherical tantalum carbide powder obtained in step (1) is placed in a calcining furnace for pre-sintering at a temperature of 1400° C. and a holding time of 60 min. After pre-sintering, a sieve with a mesh size of 800 to 1000 is used for a second screening to obtain spherical tantalum carbide particles with a particle size of 15 μm to 20 μm.
[0086] (3) Weigh the following raw materials by mass: 70 parts of the spherical tantalum carbide particles prepared in step (2), 18 parts of D 50 Tantalum carbide powder with a particle size of 0.2 μm, 0.7 parts of molybdenum disilicide (MoSi 2 ) powder, 0.6 parts of polyacrylamide, 10.7 parts of xylene, the total amount is 100 parts.
[0087] The raw materials were mixed and wet ball milled for 5 hours, with a ball-to-material ratio of 3:1 and a rotation speed of 60 r / min to prepare tantalum carbide slurry having a solid content of 88 wt%.
[0088] (4) The organic slurry prepared in the above step (3) is used to prepare a sintered tantalum carbide coating on the surface of a graphite crucible. The thickness of the prepared tantalum carbide coating is 80 μm, and the relative density is 99.1%. The coating quality is intact and has no defects such as cracks.
[0089] Example 3
[0090] (1) Tantalum carbide powder with a particle size of 0.5 μm and a purity of 99.99% is mixed with polyacrylamide to obtain a first slurry; the first slurry is then sprayed into a granulation tower by a sprayer for spray drying to obtain spherical tantalum carbide particles with good fluidity; granulated powder is obtained after drying; a sieve with a mesh size of 1000 to 1250 is then used for the first screening to obtain spherical tantalum carbide powder with a particle size of 10 μm to 15 μm. The amount of polyvinyl alcohol added is 0.5 wt% of the mass of the tantalum carbide powder; the spray drying temperature is 120°C.
[0091] (2) The spherical tantalum carbide powder obtained in step (1) is placed in a calcining furnace for pre-sintering at a temperature of 1600° C. and a holding time of 30 min. After pre-sintering, a sieve with a mesh size of 1000 to 1250 is used for a second screening to obtain spherical tantalum carbide particles with a particle size of 10 μm to 15 μm.
[0092] (3) Weigh the following raw materials by mass: 75 parts of the spherical tantalum carbide particles prepared in step (2), 15 parts of D 50 Tantalum carbide powder with a particle size of 0.5 μm, 1 part of molybdenum disilicide (MoSi 2 ) powder, 0.8 parts of polyacrylamide, 8.2 parts of n-octanol, the total amount is 100 parts.
[0093] The raw materials were mixed and wet ball milled, wherein the ball milling time was 5 hours, the ball-to-material ratio was 5:1, and the rotation speed was 50 r / min, to prepare tantalum carbide slurry. The solid content of the tantalum carbide slurry was 90wt%.
[0094] (4) The organic slurry prepared in the above step (3) is used to prepare a sintered tantalum carbide coating on the surface of a graphite crucible. The thickness of the prepared tantalum carbide coating is 50 μm, and the relative density is 99.0%. The coating quality is intact and has no defects such as cracks.
[0095] Comparative Example 1
[0096] The same as Example 1, except that no spherical tantalum carbide particles are added to the tantalum carbide powder:
[0097] (3) Weigh the following raw materials by mass: 85 parts of tantalum carbide powder, 0.5 parts of tantalum disilicide (TaSi 2 ) powder, 0.5 parts of polyvinyl alcohol, 14 parts of triolein, the total amount is 100 parts.
[0098] The raw materials were mixed and wet ball milled, wherein the ball milling time was 5 hours, the ball-to-material ratio was 5:1, and the rotation speed was 50 r / min, to prepare tantalum carbide slurry. The solid content of the tantalum carbide slurry was 80wt%.
[0099] (4) The organic slurry prepared in the above step (3) was used to prepare a sintered tantalum carbide coating on the surface of a graphite crucible. The thickness of the prepared tantalum carbide coating was 90 μm and the relative density was 97.5%. The coating quality was intact and had no defects such as cracks.
[0100] Comparative Example 2
[0101] The method is basically the same as Example 1, except that no tantalum carbide powder is added to the spherical tantalum carbide particles.
[0102] (3) Weigh the following raw materials by mass: 85 parts of the spherical tantalum carbide particles prepared in step (2), 0.5 parts of tantalum disilicide (TaSi 2 ) powder, 0.5 parts of polyvinyl alcohol, 14 parts of triolein, the total amount is 100 parts.
[0103] The raw materials were mixed and wet ball milled for 5 hours, with a ball-to-material ratio of 5:1 and a rotation speed of 50 r / min to prepare tantalum carbide slurry having a solid content of 87 wt%.
[0104] (4) The organic slurry prepared in the above step (3) is used to prepare a sintered tantalum carbide coating on the surface of a graphite crucible. The thickness of the prepared tantalum carbide coating is 105 μm and the relative density is 96.8%. A small number of tiny pores exist in the coating.
[0105] Comparative Example 3
[0106] The method is basically the same as Example 2, except that the preparation process of the spherical tantalum carbide particles is not pre-sintered. The specific steps are as follows:
[0107] (1) Tantalum carbide powder with a particle size of 0.2 μm and a purity of 99.99% is mixed with polyacrylamide to obtain a first slurry; the first slurry is then sprayed into a granulation tower by a sprayer for spray drying to obtain spherical tantalum carbide particles with good fluidity; granulated powder is obtained after drying; a sieve with a mesh size of 800 to 1000 is then used for the first screening to obtain spherical tantalum carbide powder with a particle size of 15 μm to 20 μm. The amount of polyvinyl alcohol added is 0.5 wt% of the mass of the tantalum carbide powder; the spray drying temperature is 100°C.
[0108] (2) Weigh the following raw materials by mass: 70 parts of tantalum carbide spherical powder prepared in step (1), 18 parts of D 50 Tantalum carbide powder with a particle size of 0.2 μm, 0.7 parts of molybdenum disilicide (MoSi 2 ) powder, 0.6 parts of polyacrylamide, 10.7 parts of xylene, the total amount is 100 parts.
[0109] The above raw materials were mixed and wet ball milled, wherein the ball milling time was 3 hours, the ball-to-material ratio was 1:1, and the rotation speed was 60 r / min, to prepare tantalum carbide slurry. The tantalum carbide spherical powder was broken during the ball milling process, and the solid content of the tantalum carbide slurry was 75wt%.
[0110] (3) The organic slurry of this comparative example was used to prepare a sintered tantalum carbide coating on the surface of a graphite crucible. The thickness of the tantalum carbide coating was 108 μm and the relative density was 96.3%. A small amount of cracks existed in the coating.
[0111] The raw materials of the organic slurry in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3 of the present application are shown in Table 1; the process parameters for preparing spherical tantalum carbide particles are shown in Table 2; and the performance test results are shown in Table 3.
[0112] Table 1
[0113]
[0114] Table 2
[0115]
[0116] Table 3
[0117]
[0118] As can be seen from Tables 1 to 3 above, in Comparative Example 1, only tantalum carbide powder with a smaller particle size is used, and the solid phase content of the obtained tantalum carbide slurry is only 80wt%, which affects the density and strength of the tantalum carbide coating. In Comparative Example 2, only spherical tantalum carbide particles with a larger particle size are used, and the solid phase content is improved, but the sintering activity of tantalum carbide is significantly reduced, thereby reducing the relative density of the sintered tantalum carbide coating. In the process of preparing spherical tantalum carbide particles in Comparative Example 3, no low-temperature pre-sintering treatment is performed, and its sintering activity is lower than that of Examples 1 to 3. In addition, the powder in Comparative Example 3 is not spheroidized and has a fine particle size, which significantly increases the viscosity of the slurry, resulting in a decrease in the solid phase content.
[0119] The tantalum carbide slurry prepared in Examples 1 to 3 has a higher solid content, and the coating obtained by sintering has a higher relative density, which can meet the performance requirements of the graphite crucible surface coating.
[0120] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0121] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing tantalum carbide slurry, characterized in that: The steps include: Mixing tantalum carbide powder and a binder to obtain a first slurry; The first slurry is subjected to spray drying, first screening, pre-sintering and second screening in sequence to obtain spherical tantalum carbide particles; the particle size of the spherical tantalum carbide particles is 10 μm to 30 μm; The spherical tantalum carbide particles are mixed with the tantalum carbide powder, a sintering aid, a non-ionic polymer binder and an organic solvent to obtain a mixture; the particle size of the tantalum carbide powder is 0.05 μm to 0.5 μm; The mixture is wet-milled to obtain tantalum carbide slurry.
2. The method for preparing tantalum carbide slurry according to claim 1, characterized in that: In terms of mass percentage, the mixture includes: 65 to 80 parts of spherical tantalum carbide particles, 5 to 20 parts of tantalum carbide powder, 0.5 wt % to 1 part of sintering aid, 0.5 to 1 part of non-ionic polymer binder and 8 to 14 parts of organic solvent.
3. The method for preparing tantalum carbide slurry according to claim 1, characterized in that: In terms of mass percentage, the mixture includes: 70 to 75 parts of spherical tantalum carbide particles, 15 to 18 parts of tantalum carbide powder, 0.7 wt % to 1 part of sintering aid, 0.6 to 0.8 parts of non-ionic polymer binder and 8.2 to 10.7 parts of organic solvent.
4. The method for preparing tantalum carbide slurry according to any one of claims 1 to 3, characterized in that: The particle size of the tantalum carbide powder is 0.1 μm to 0.5 μm.
5. The method for preparing tantalum carbide slurry according to any one of claims 1 to 3, characterized in that: The tantalum carbide slurry satisfies at least one of the following conditions: (1) The sintering aid is selected from one or more of tantalum disilicide, molybdenum disilicide, pyrolytic carbon black, aluminum oxide and yttrium oxide; (2) The particle size of the sintering aid is 0.5 μm to 5 μm; (3) The organic solvent is selected from one or more of ether, anhydrous ethanol, butanone, n-octanol, triolein, toluene, xylene and isopropanol; (4) The nonionic polymer binder is selected from one or more of polyacrylamide, polyethylene oxide, polyurethane, polyvinyl alcohol, polyaniline and polyethylene terephthalate.
6. The method for preparing tantalum carbide slurry according to any one of claims 1 to 3, characterized in that: The preparation method satisfies at least one of the following conditions: (1) In the wet ball milling step, the ball milling time is 2 h to 6 h, the ball to material ratio is (1 to 5):1, and the rotation speed is 50 r / min to 500 r / min; (2) The temperature of the spray drying process is 80°C to 120°C; (3) The pre-sintering temperature is 1200°C to 1600°C, and the holding time is 30min to 120min; (4) The mesh sizes of the first screening and the second screening are independently selected from 500 mesh to 1250 mesh.
7. The method for preparing tantalum carbide slurry according to any one of claims 1 to 3, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, methyl cellulose and polyacrylic acid; (2) Based on the mass of the tantalum carbide powder in the first slurry, the amount of the binder added is 0.1wt%~0.5wt%.
8. A tantalum carbide slurry, characterized in that: The tantalum carbide slurry is prepared by the preparation method of any one of claims 1 to 7.
9. A tantalum carbide coating, characterized in that: The raw material for preparing the tantalum carbide coating includes the tantalum carbide slurry as claimed in claim 8.
10. A tantalum carbide product, characterized in that: Comprising the tantalum carbide coating of claim 9.
Citation Information
Patent Citations
Tantalum carbide coating, preparation method of tantalum carbide coating, carbonaceous structural member and application of carbonaceous structural member
CN117776781A
Preparation method of high-solid low-viscosity photocuring ceramic slurry
CN118184320A
Tantalum carbide sintered compact, method for producing the same, molding die, and target material
JP2009137789A
High heat-resistant member and method for producing the same
JP2013193943A
